Performa Komunikasi dalam Pengembangan Kapasitas Kewirausahaan Sosial pada Badan Usaha Milik Desa (BUMDes) Panggung Lestari Desa Panggungharjo, Kabupaten Bantul - Aida Vitayala S Hubeis; Sarwititi Sarwoprasodjo; Basita Ginting; Risyart A Far Far; Kusuma Satria (Jurnal Penyuluhan, 2022)
Village-Owned Enterprises (BUMDes) is an institution that focuses on the economy that was formed in rural Indonesia through the use of local resources. The study aims to (1) to analyze the communication performance of members in constructing organizational culture on the dimensions ritual, desire, social, political and enculturation in the Panggungharjo BUMDes Village. (2) Analyzing communication performance developing social entrepreneurship capacity on the dimension of social value in Panggungharjo BUMDes business units. The study using the qualitative approach through interviews with 20 informants consisting of advisors, supervisors, BUMDes managers and community groups in collaboration with Panggungharjo BUMDes, Bantul Regency. The results showed that performance communication of members business units in constructing the organizational culture of BUMDes Panggungharjo Village through the dimensions of task rituals, personal rituals and social rituals. All potential rituals run well in the flexibility of tasks between sections, divisions, units and forge togetherness and intimacy among members and managers. Communication performance in BUMDes includes political performance, enculturation, social performance and desire performance. Communication performance functions well in instilling the values ​​of social entrepreneurship through exemplary and togetherness. Communication performance developing social entrepreneurial capacity in the dimension social value is togetherness in the growth of local economic activity.